Origin and history of Phoxinus (Cyprinidae) introductions in the Douro basin (Iberian Peninsula): an update inferred from genetic data - Garcia-Raventós, A. (2020)
The number of non-native freshwater fishes in the Iberian Peninsula has been greatly increasing. In this study, individuals of the genus Phoxinus were detected in 18 out of 138 stream sites sampled across the Douro Basin in 2017 and 2018. A total of 26 individuals were barcoded using partial cytochrome c oxidase subunit I (COI) and cytochrome b (cytb) genes for species identification and determination of geographical origin. Molecular data provided the first record of a second Phoxinus species in western Douro (Portugal, Iberian Peninsula), with haplotypes closely matching those found in the Charente River (southern France). This species is suspected to be a recent introduction associated with the use of minnows as live bait by freshwater anglers, which was facilitated by human movements between France and Portugal. Individuals from watercourses in eastern Douro (Spain) were genetically assigned to Phoxinus bigerri, an introduced species previously known for that region, which confirms reports of introduction events from Ebro to Douro Basin probably also related to freshwater angling and facilitated by geographic proximity. The potential ecological impacts of this genus in the region are unknown and need further investigation.